2016
DOI: 10.1136/injuryprev-2016-042021
|View full text |Cite
|
Sign up to set email alerts
|

“I wasn't texting; I was just reading an email …”: a qualitative study of distracted driving enforcement in Washington State

Abstract: Background In response to the rise of distracted driving, many countries and most US states have adopted laws to restrict the use of handheld phones for drivers. Specific provisions of each law and the overall social mores of distracted driving influence enforceability and impact. Objectives Identify multilevel interdependent factors that influence distracted driving enforcement through the perspective of police officers. Design/methods We conducted focus group discussions with active duty law enforcement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 16 publications
0
10
2
Order By: Relevance
“…45 Qualitative research also has shown that police officers have a sense of discomfort in ticketing for cellphone-related distracted driving, as it can be ambiguous what drivers are actually doing with their phone while driving along with the low rate of admittance from drivers on their engagement in distracted driving. 46,47 Along with the effectiveness of cellphone bans, culture and environment have critical roles in shaping young drivers' behavior. 48,49 As driving is a learned behavior, parents/guardians serve as the primary role models for teen drivers and contribute to the overall traffic safety culture.…”
Section: One Possible Explanation For the Lack Of An Association Betwmentioning
confidence: 99%
“…45 Qualitative research also has shown that police officers have a sense of discomfort in ticketing for cellphone-related distracted driving, as it can be ambiguous what drivers are actually doing with their phone while driving along with the low rate of admittance from drivers on their engagement in distracted driving. 46,47 Along with the effectiveness of cellphone bans, culture and environment have critical roles in shaping young drivers' behavior. 48,49 As driving is a learned behavior, parents/guardians serve as the primary role models for teen drivers and contribute to the overall traffic safety culture.…”
Section: One Possible Explanation For the Lack Of An Association Betwmentioning
confidence: 99%
“… 45 Drivers may doubt that texting-only bans are enforceable. 44 , 46 For example, drivers may believe that if stopped by a police officer, they can avoid a citation by claiming they were calling, not texting. A comprehensive ban is easier to enforce, because it is impossible for police to differentiate texting from dialing and other phone use.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive ban is easier to enforce, because it is impossible for police to differentiate texting from dialing and other phone use. 44 , 46 A cross-sectional comparison of 14 US states found that more citations were issued when both calling and texting were prohibited, compared with texting-only (2,022 versus 14 per 100,000 person–years). 47 …”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research has also shown that police officers have a sense of discomfort in ticketing for cellphone-related distracted driving. As it can be ambiguous what drivers are actually doing with their phone while driving, along with the low rate of admittance from drivers on their engagement in distracted driving (Rudisill et al 2019 ; Nevin et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%